False‐Positive Results in Metagenomic Virus Discovery: A Strong Case for Follow‐Up Diagnosis. Issue 4 (10th June 2014) - Rosseel, T.; Pardon, B.; De Clercq, K.; Ozhelvaci, O.; Van Borm, S.
Summary A viral metagenomic approach using virion enrichment, random amplification and next‐generation sequencing was used to investigate an undiagnosed cluster of dairy cattle presenting with high persistent fever, unresponsive to anti‐microbial and anti‐inflammatory treatment, diarrhoea and redness of nose and teat. Serum and whole blood samples were taken in the predicted hyperviraemic state of an animal that a few days later presented with these clinical signs. Bioinformatics analysis of the resulting data from the DNA virus identification workflow (a total of 32 757 sequences with average read length 335 bases) initially demonstrated the presence of parvovirus‐like sequences in the tested blood sample. Thorough follow‐up using specific real‐time RT‐PCR assays targeting the detected sequence fragments confirmed the presence of these sequences in the original sample as well as in a sample of an additional animal, but a contamination with an identical genetic signature in negative extraction controls was demonstrated. Further investigation using an alternative extraction method identified a contamination of the originally used Qiagen extraction columns with parvovirus‐like nucleic acids or virus particles. Although we did not find any relevant virus that could be associated with the disease, these observations clearly illustrate the importance of using a proper control strategy and follow‐up diagnostic tests in any viral metagenomic study.